2016
DOI: 10.1021/acs.jpcc.6b04605
|View full text |Cite
|
Sign up to set email alerts
|

Insights into CO2 and CH4 Adsorption by Pristine and Aromatic Amine-Modified Periodic Mesoporous Phenylene-Silicas

Abstract: This version is available at https://strathprints.strath.ac.uk/56714/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Recently, we described and understood the amination of the Ph-PMO (NH2-Ph-PMO) with different pore sizes (2.4 -3.7 nm) and tested their performance on the CO2 and CH4 adsorption. 16 We observed that the CO2 affinity on these materials can be directly correlated to the amount of T 2 free silanols and the amination on the phenylene moieties is only effective on materials with small pore size, improving the affinity to the CO2 gas. In the present work, non-functionalized (Ph-PMO) and amine functionalized Ph-PMOs (NH2-Ph-PMO), having pore sizes of approximately 2.5 nm, were synthesized according to previously reported procedures.…”
Section: Introductionmentioning
confidence: 80%
“…Recently, we described and understood the amination of the Ph-PMO (NH2-Ph-PMO) with different pore sizes (2.4 -3.7 nm) and tested their performance on the CO2 and CH4 adsorption. 16 We observed that the CO2 affinity on these materials can be directly correlated to the amount of T 2 free silanols and the amination on the phenylene moieties is only effective on materials with small pore size, improving the affinity to the CO2 gas. In the present work, non-functionalized (Ph-PMO) and amine functionalized Ph-PMOs (NH2-Ph-PMO), having pore sizes of approximately 2.5 nm, were synthesized according to previously reported procedures.…”
Section: Introductionmentioning
confidence: 80%
“…Thus far, selectivity for CO 2 /CH 4 separation for different functionalized PMOs has been evaluated by using experiments [30,31], while the CO 2 and CH 4 adsorption mechanisms involved in this materials were clarified using periodic density functional theory (DFT) calculations [30]. In fact, as we have observed, experimental gas adsorption data and computational studies are in good agreement and such DFT results proved also useful to guide the preparation of more efficient PMO materials.…”
mentioning
confidence: 78%
“…Additionally, Ph-PMOs display a narrow distribution of both meso-and molecular-scale periodicities; a clear advantage for adsorbate diffusion within the pore channels. Moreover, we have seen [30,31] that the modification of the Ph-PMO with amine groups allows the optimization of their properties for the separation of CO 2 /CH 4 , by improving the interaction with the CO 2 molecule. Recently, we demonstrated that aminopropyl groups grafted to the free silanols of Ph-PMO promote selectivity for CO 2 /CH 4 separation making the resulting APTMS@Ph-PMO so far the most selective of all PMOs applied in this field, at 25 °C adsorbing 26.1 times more CO 2 than CH 4 , as determined by the ratio of Henry constants [30].…”
mentioning
confidence: 99%
“…demonstrated that amine groups could be functionalized in the PMOs through mononitration with nitric acid in the presence of sulphuric acid, followed by the reduction with tin chloride and HCl. The amine‐functionalized samples showed higher selectivity for the adsorption of CO 2 molecules in comparison with the CH 4 molecules . The same group also manipulated the amine‐functionalized PMOs for the formation of dialkylated amine through the microwave‐assisted approach.…”
Section: Synthesis Of Organo‐functionalized Molecular Sievesmentioning
confidence: 99%